Evolution and interaction mechanisms of China’s high-performing national healthcare system - Chong Feng; Feiyang Chen; Ziwei Ye; Fenling Zhang (BMC Health Services Research)
Abstract Objectives This study aims to identify the dimensions and evolutionary pathways of China’s high-performing national healthcare system, as well as the interaction mechanisms between the digital and traditional healthcare dimensions. Methods This study first constructs a high-performing healthcare evaluation index comprising four dimensions: digital healthcare, healthcare resource allocation, healthcare output, and healthcare effectiveness. It next presents a multilevel structural dynamic factor model to examine the evolutionary pathway of China’s national healthcare system. It then analyses the interaction mechanism of each healthcare dimension based on the impulse response function. Results First, the upward trend in the overall performance of China’s high-performing national healthcare system demonstrates that it is significantly improving. Second, the overall performance of China’s high-performing national healthcare system has been most impacted by healthcare effectiveness and least impacted by healthcare output. The performance is trending upward for digital healthcare and healthcare resource allocation but downward for healthcare output and effectiveness. Third, increasing healthcare resource allocation and output promotes digital healthcare. The improvement in digital healthcare performance significantly and positively impacts healthcare effectiveness, while having weaker effects on healthcare resource allocation and healthcare output. Conclusions The performance of China’s high-performing national healthcare system is improving. However, healthcare resource allocation and health outcomes require further optimisation, and the integration capacity of traditional healthcare with digital healthcare must be strengthened.